Medical Therapeutics Derived from Leeches (Phy. Annelida; Cl. Hirudinea) - Clarke, Christopher Everett Warren (MacEwan University Student eJournal, 2016)
Of all blood feeding invertebrates, few are more notorious than leeches. Throughout their existence as ectoparasites, leeches have evolved to release biological molecules in their saliva that act to counter the responses of the prey’s body to vascular trauma. Inadvertently, these very molecules have been used by humans for centuries for medicinal purposes; however, it is only recently that their cellular action has been elucidated. As a result, these compounds have been isolated and mass produced to treat a wide variety of conditions ranging from heart attack to Alzheimer’s disease and continued work suggests that these isolates will be an important future treatment for metastasis.